2005
DOI: 10.1111/j.1444-2906.2005.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration of anadromous white-spotted charr Salvelinus leucomaenis, as determined by otolith strontium : calcium ratios

Abstract: The migratory history of anadromous white-spotted charr Salvelinus leucomaenis collected from Japanese coastal waters, was examined in terms of strontium (Sr) and calcium (Ca) uptake in the otolith, by means of wavelength dispersive X-ray spectrometry using an electron microprobe. Otolith Sr concentration or Sr : Ca ratios of anadromous S. leucomaenis , fluctuated strongly along the life history transect in accordance with the migration (habitat) pattern from sea to fresh water. The anadrmous S. leucomaenis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Similar observations were made by Kafemann et al (2000), Arai et al (2005), and Elsdon and Gillanders (2006).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similar observations were made by Kafemann et al (2000), Arai et al (2005), and Elsdon and Gillanders (2006).…”
Section: Discussionsupporting
confidence: 75%
“…The noted differences in percentage shares of calcium might be linked with the level of total mineral matter dissolved in water (TDS), this being much greater in the waters Humphreys et al (2006) analysed. Bijvelds et al (1997), Arai et al (2005), and Arai and Hirata (2006) all reported that a higher level of salinity in water will be associated with the partial expulsion of calcium and sodium ions from bone structure, their place being taken by magnesium, strontium, and potassium ions. Similar trends were observed for the opercula of perch living in different environments of the Oder Estuary; the opercular contents of magnesium, strontium, and potassium were directly proportional to -and correlated significantly with -the concentration of chloride and sulphate ions, as well as the total dissolved mineral matter (TDS) in estuarine waters (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Strontium (Sr) and calcium (Ca) in otoliths are of particular interest for these studies. Higher deposition of Sr into otoliths is found in sea migrants than in freshwater residents, and Sr alternates with Ca in bony tissues in proportion to the levels in the ambient water (Arai et al , 2005). In estuaries, the Sr:Ca ratio in the otoliths of many diadromous fishes are significantly related to the salinity of the surrounding fresh, brackish and sea water during their life histories (Campana, 1999; Secor & Rooker, 2000; Arai, 2002; Arai et al , 2003 a ; Tzeng et al , 2003), implying that these are important natural tracers of the habitat use histories of estuarine fishes.…”
Section: Introductionmentioning
confidence: 99%
“…This correlation confirmed earlier observations, showing a more frequent use of magnesium in building the skeleton, regardless of the amount of available sodium (Bijvelds at al. 1997;Arai at al. 2005;Arai, Hirata 2006).…”
Section: Discussionmentioning
confidence: 99%
“…(1997), Arai et al (2005), and Arai, Hirata (2006) which ascertained that an increase in water salinity resulted in calcium and sodium ions being utilized less in the skeletal structure in favor of magnesium, strontium and potassium ions. Similar correlations were also observed in species inhabiting the Pomeranian Bay.…”
Section: Discussionmentioning
confidence: 99%